ANALISIS KONSTRUKSI SOSIAL DAN INTERAKSI SIMBOLIK RITUAL ADAT MEPE KASUR PADA MASYARAKAT DESA KEMIREN - Inggritia Zahrotunnisa; I Nyoman Ruja (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
Mepe kasur traditional ritual is a still sustainable local wisdom coming from Banyuwangi, where people dry the black and red mattresses together in front of the house. This study aims to analyze the implementation procedure and the social construction through internalization, objectification, and externalization processes and symbolic interaction contained in the Mepe kasur traditional ritual. This study uses a qualitative approach with interview and observation being data collection methods. This study yielded three findings. Firstly, the Mepe kasur traditional ritual consisted of 1) the mattress was dried in the sun from morning until noon; 2) the mattress was swept and beat using a woven stick until the dust came out; 3) past noon, the mattress was put into the bed at home, 4) people went to do pilgrimage to the tomb of the great-grandfather Cili; 5) tumpeng sewu. Secondly, based on the social construction, the Mepe kasur traditional ritual has entered the processes of internalization, objectification, and externalization. Thirdly, in symbolic interaction, the Mepe kasur traditional ritual is intended to maintain the continuity of a family, where the mattress is a place for taking a rest and discussing to married couples.